The Exploration of Interlocutors and Technological Support Systems on Student’s Speaking Skill Development - Muhammad Falka Alwi; Mhd Rasid Ritonga; Muslem Muslem (Transpublika Publisher, 2026)
Speaking skill development remains a major challenge for English as a Foreign Language (EFL) learners due to limited opportunities for authentic communication, and insufficient speaking practice. This study explored the roles of interlocutors and technological support systems in supporting students’ speaking development at IAIN Langsa. The participants were five English department students at IAIN Langsa. They were selected through purposive sampling based on their experiences in classroom interaction, online communication, and technology-assisted speaking practice. This study employed an exploratory qualitative design. Data were collected through semi-structured interviews and forum group discussion and analyzed using thematic analysis, including coding, categorization, theme development, and interpretation. The findings indicate that interaction with classmates, online speaking partners, and interlocutors contributed significantly to students’ fluency, spontaneity, and communicative adaptability. Technological tools such as WhatsApp, YouTube, and ELSA Speak supported autonomous learning, pronunciation improvement, and communication confidence through repeated exposure and continuous practice. Despite these benefits, participants continued to face challenges related to speaking anxiety, limited vocabulary, and inconsistent opportunities for speaking practice. The study concludes that speaking development is enhanced when authentic communicative interaction is integrated with technology-assisted learning environments. The findings suggest that EFL instructors should design interaction-rich learning activities and incorporate supportive digital technologies to foster more effective and sustainable speaking development.